Morfologia comparada dos ductos genitais femininos e gonópodos masculinos de caranguej.s Eubrachyura (Saint Laurent, 1980) - Souza, Leonardo Peres de [UNESP] (2013)
Comparative works on the morphological characteristics of female genital ducts and male gonopod in crabs are scarce. Besides, little is known about the role of the genital ducts on the fertilization process or how the sperm is transferred to them, via male gonopods. The present work makes histological analyses of the female genital ducts and male gonopods on different Eubrachyura crabs families. Samples were collected on the coastline of the State of Ceará, between years 2010 and 2013. Males and females from seven different species of Eubrachyura were collected. The females were dissected and the female reproductive system was analyzed macroscopically and microscopically (light microscopy). Male gonopods were removed, fixed and processed for histological analysis and scanning electron microscopy. Anatomically, female reproductive system follows a pattern, consisting on a pair of elongated ovaries and a pair of genital ducts that extends to the exterior. The genital ducts of all species analyzed were constituted of four regions: oviduct, seminal receptacle, vagina and gonopore (vaginal opening or vulva). The ovaries can be connected to the seminal receptacle on the ventral or dorsal region. The morphohistological characteristics found on the genital ducts, mainly the vagina shape and the type of secretory epithelium of the seminal receptacle, indicates that these were related to taxon phylogeny. It was not possible to evaluate the exact fertilization site, although, the results allow inferring that the fertilization process begins at the seminal receptacle and concludes at the pleopods. We conclude that, among Eubrachyura, sperm transfer is performed by the association of the papille penile, first and second gonopods. The last two are covered in various setae types that, depending on the morphology and location, may have functions like protection, filtering, chemo and mechanoreception. Histologically, the gonopods of the analyzed...